Quantificação relativa dos níveis transcricionais dos genes LSP1 e RNASEL em tecido prostático e sangue periférico de pacientes com câncer de próstata e hiperplasia prostática benigna - Carvalho, Washington João de (2009)
Several studies have been conducted in an attempt to discover novel biomarkers that are able to distinguish prostate cancer (PCa) from benign prostatic hyperplasia (BPH) with the purpose of helping or even supplant the current diagnostic methods, the total serum PSA levels and the digital rectal examination (DRE), mainly due to their deficiencies. Our study aimed to evaluate, by real time PCR, the potential use of the LSP1 (Leukocyte Specific Protein 1) e RNASEL (Ribonuclease L 2 ,5 oligoisoadenilato sintetase dependent) genes as biomarkers of prostate cancer in tissue samples of patients with PCa and BPH, and also in the peripheral blood of patients and healthy volunteers (control group); and verify their efficiency as a possible diagnostic method for this disease. A prior screening of 630 men, 170 men over 45 years old were included in the sampling because of suspicious DRE and/or PSA>2.5 ng/mL, with indication of prostatic biopsy, which 60 were PCa and 30 BPH patients. A group of 60 healthy volunteers men with a mean age of 22 years was used as control. Total RNA from these samples were converted into cDNA and transcriptional levels of biomarkers were measured by relative quantification in real-time PCR. The cutoff value was established for all tests from a ROC curve estimation. There was no statistical difference in the levels of expression in the prostate tissues between PCa and BPH groups. However, in the peripheral blood, higher LSP1 levels presented a 3.5-fold higher odds to occur in BPH than in PCa. Similarly, higher levels of RNASEL presented a 3.2-fold more likely to occur in PCa samples than in BPH ones. Considering the cut-off values for both genes, the duplex analysis (LSP1 negative and RNASEL positive; 1.79 and 1.25, respectively) generated an odds ratio of 4.5-fold for PCa diagnostics, with 80% sensitivity, 96% specificity, and 91% accuracy. This is the first report on the application of the LSP1 and RNASEL genes in prostate cancer diagnostics, and also the first to use contrasting differential responses of the two genes, where the LSP1 detects mainly the BPH status and the RNASEL detects the cancer, which together are able to discriminate the prostate cancer cases with 91% precision. These factors showed the ability for applicability in clinical practice of these biomarkers, reducing the negative biopsy and without causing discomfort to patients.